The Effect of Competence, Doctor Consultation Time and Facility Availability on Patient Complaints at the Emergency Ed at Permata Hospital, Depok - Dewi Rosenni Sijabat; Rian Andriani; Achmad Dheni Suwardhani (Research of Service Administration Health and Sains Healthys, 2025)
Emergency Department (ED) services are crucial as they directly impact patient survival. A decline in ED visits at Permata Depok Hospital in 2024 and early 2025 has raised concerns, particularly related to patient complaints shared via social media. This study aims to analyse the influence of healthcare workers’ competence, doctor consultation time, and facility availability on patient complaints in the hospital’s ED. This is a quantitative study with a cross-sectional design, involving 93 respondents selected using the Slovin formula from a population of 1,180 patients. Data were collected through a Likert-scale questionnaire and analysed using chi-square tests and logistic regression. The results show that all three variables significantly affect patient complaints (p-value < 0.05), with facility availability especially basic sanitation like soap, tissue, and clean water emerging as the most dominant factor. Managerial implications include the need to prioritize supporting facilities, implement SOPs and regular sanitation audits, adopt rapid reporting systems using QR codes, and make data-driven decisions through satisfaction surveys and WASH-FIT audits. Future research is recommended to expand variables, apply mixed-methods approaches, conduct inter-hospital comparisons, and monitor intervention outcomes.